Single Machine Total Absolute Differences Penalties Minimization Scheduling with a Deteriorating and Resource-Dependent Maintenance Activity. (14th June 2017) - Wang, Zhenyou; Xiao, Cuntao; Lin, Xianwei; Lu, Yuan-Yuan
Abstract: In this paper, we consider a single-machine scheduling problem with a deteriorating and resource-dependent maintenance activity, that is, the duration of the maintenance is assumed to be dependent both on its starting time and on the resource allocated to it. Our goal is to determining the schedule of jobs, the position to schedule the maintenance activity and the amount of additional resource allocated to it such that the total cost of the total absolute differences in completion times and the resource are minimized. We show that the problem remains polynomially solvable.